Eutrophication and Hypoxia Diminish Ecosystem Functions of Benthic Communities in a New England Estuary - Hale, Stephen S.; Cicchetti, Giancarlo; Deacutis, Christopher F. (Frontiers in Marine Science, 2016)
Excessive input of nitrogen to estuaries and coastal waters leads to eutrophication; the resulting organic matter over-enrichment of sediments and seasonal hypoxia of bottom water have significant deleterious effects on benthic community biodiversity, abundance, and biomass. Our goal was to better understand how these losses carry through to impairment of key ecosystem functions of benthic communities. Recent management efforts to address eutrophication have reduced nitrogen loading to several estuaries of the Virginian Biogeographic Province (northeast United States). How the ecosystems will respond remains to be seen. Using Narragansett Bay as an example estuary within this Province, we compared measures of community structure and function from stations in seasonally hypoxic areas with stations in normoxic areas. We analyzed a benthic data set spanning 20 years (1990-2010) and 155 stations, along with ancillary data from other sources. Hypoxic areas had half the species richness, many fewer rare species, and lower biomass. Benthic communities in the hypoxic areas had a significantly different abundance structure, were at an earlier successional stage, and bioturbated the sediments to a depth about one-fifth that of the normoxic areas. On average, sediments in the hypoxic areas took up more oxygen—used for aerobic metabolism and oxidation of reduced compounds from anaerobic metabolism—than those in normoxic areas. Sediments released into the overlying water two to three times more ammonium and phosphate. Mean flux of dissolved oxygen into the sediments of hypoxic areas and mean net flux of nitrogen gas (from sediment denitrification) out were slightly higher. Eutrophication-driven over-enrichment of organic matter, along with seasonal hypoxia in the northern part of the Bay have led to degradation of benthic community structure and function, which have serious implications for sustainable provision of ecosystem services. We quantified fifteen stressor-response relationships that can help understand how, following a reduction in nitrogen inputs, a recovery of benthic ecosystem functions in hypoxic areas could proceed.